Influence of Type of School on Sport Practice and Leisure Activities of Schoolchildren - Arufe-Giráldez, Victor (2017)
Background: Recent researches have shown the importance of extracurricular activities and leisure time in children of school age, especially within today’s society where the increasing labour activity of families makes difficult to spend time with children. In this sense, sport practice has a central role, as it will help to combat sedentary lifestyle produced by digital leisure. Aims: This study aims to determine the extracurricular sports and leisure activities done by a sample of primary school students, analysing its relation to the type of school in which they are enrolled. Design: A descriptive and cross-sectional study of multifactorial and univariate design was conducted. Respondents: A total of 786 students from Primary Education participated in this research. They were selected by using a random cluster sampling. Measurements: This study employed an Ad-hoc questionnaire consisting of 12 items related to extra-curricular sport practice. Analysis: SPSS 22.0 software was used for statistical analyses by using cross tables, ANOVA or T of Student depending on the nature of the variables. Results: The results showed acceptable measures of sports practiced, high percentages of screen leisure and low measurements of time which is spent in reading and with peers. According to the type of school, it was revealed that the schoolchildren of private schools practiced more sports, mainly in teams. Students in public schools preferred individual sports and spending more time with friends and in digital entertainment. Thus, the relationship between the type of school and non-curricular activities is shown, mainly for reasons of ideology and facilities.